Using Mobile Technology for Studying library Spaces - Thompson, Susan (Qualitative and Quantitative Methods in Libraries; Vol 4 No 2 (2015): June 2015 Issue, 2017)
Traditional methods for tracking library building use, such as gate counts, provide little information on what patrons actually do once they are in the library. New methods for studying space usage, such as observation of user behaviors throughout the library‘s study spaces, can be labor intensive. Mobile technologies provide an efficient method to track observations of patron‘s study behaviors and provides quantitative data for the typically qualitative observation methodology.